Determining motion saliency in videos - Tan, Angeline Chern Kai. (2010)
This Final Year Project describes an algorithm for obtaining and extracting information that attracts user attention in a video clip. The key factors that make a region attractive are the motion that happened in a video, the low-level features like image orientation and intensity and also the semantic influence in a video.